Digital Agriculture Profile: Kenya - Osiemo, Jamleck; Girvetz, Evan Hartunian; Hasiner, Eva; Schroeder, Kateryna; Treguer, David; Juergenliemk, Armine; Horst, Alexandra; Jarvis, Andy; Kropff, Wietske (Food and Agriculture Organization of the United Nations, 2021)
This Digital Agriculture Profile for Kenya leverages the expertise of stakeholders to evaluate the current landscape of digital agriculture in Kenya, including its key players across value chains, the main barriers they face, and the potential to overcome these barriers through the adoption of innovative technologies.